Eksplorasi Alat Musik Keteng-Keteng Terhadap Bangun Ruang Sisi Lengkung Tabung - Sitepu, Edi Petra; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the relationship between the traditional Keteng-keteng musical instrument from Batak Karo and the concept of curved tube space construction from an ethnomathematics perspective. The research uses Spradley's ethnographic approach with data collection techniques through observation, interviews, and documentation. The data obtained is analyzed using Spradley's ethnographic analysis model, which includes domains, taxonomy, components, and cultural themes, thereby providing a deep understanding of the relationship between cultural objects and mathematical concepts. The results of the study show that the bamboo structure of Keteng-keteng is tube-shaped, characterized by two circular bases and a curved cover. This finding indicates that Keteng-keteng can be used as an ethnomathematics learning medium to introduce the concept of tubes to students. In addition, this study also contributes to efforts to preserve local culture through the integration of traditional elements into mathematics learning.